Three dimensional real Lie bialgebras - Farinati, Marco Andrés (2015)
By different methods, we classify the real three dimensional Lie bialgebras and give their automorphism groups; in case of coboundary Lie bialgebras, the corresponding coboundaries r ∈Λ2g are listed.